1 Fed. Reg. 668, 674, National Park Service Rules and Regulations (1936) § 8 - (:unkn) unknown (General Publisher, 1936)
Prohibited firearms, explosives, traps, seines, and nets within the parks and monuments under federal control.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES